The role of artificial lighting techniques in forming sacred expressions at the sanctuary of the St. Laurentius Catholic Church Bandung, Indonesia (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The interpretation differences of the policies implemented by the Second Vatican Council have a significant influence on the increasingly diverse views and manifestations of the sacred expressions in the Catholic Church. Therefore, this research focuses on the sacred expression of the Sanctuary as the most important space of the Catholic Church. It was carried out at St. Laurentius Catholic Church Bandung because it applies various artificial lighting techniques to its worship space. Furthermore, this research discusses how and to what extent artificial lighting techniques are able to support the sacred expression of the contemporary Catholic Church Sanctuary. Data were quantitatively collected through working drawings, measuring the illumination level in the work area, and determining the brightness of space-forming materials. Meanwhile, data were also qualitatively collected through field observations and visual recordings. The analysis process was used to analyze the architectural sacredness, such as orientation, hierarchy, balance, and symbols. In addition, visual analysis was used for clarity, uniformity, balance, brightness, and spatial intimacy. The results showed that artificial lighting techniques play a significant role in forming sacred expressions of the Sanctuary of the St. Laurentius Catholic Church Bandung.
Keywords: Artificial lighting technique; Sacred expression; Sanctuary; St. Laurentius Catholic Church Bandung